Examining the impact of environmental product innovation on perceived brand value considering the mediating role of ethical- aspects in the home appliance industry - Hamidreza Talaie (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Increasing consumer attention to environmental and ethical issues has driven brands towards implementing innovative and sustainable policies. Therefore, in the current era, environmental innovation has emerged as a fundamental element in marketing strategies and brand management. Moreover, ethical aspects are very important to customers and are among the key concepts of brand value. Hence, this research examines the impact of environmental innovation of National home appliance products on perceived value through the mediating role of ethical aspects.Methodology: This research is applied in purpose and descriptive-correlational in method. The statistical population of this research consists of customers of national home appliance brands. In this study, a convenience sampling method was used. To collect data, a standardized questionnaire was used, whose validity was confirmed by calculating content, convergent, and divergent validity, and its reliability was confirmed through the Cronbach's alpha index. In statistical analysis, the structural equation modeling approach was used.Findings: Based on the research results, environmental product innovations have a positive and significant impact on perceived brand value, open-mindedness, and customer privacy. Additionally, open-mindedness and customer privacy have a positive and significant impact on perceived brand value. Furthermore, open-mindedness and customer privacy play a mediating role in the relationship between environmental product innovations and perceived brand value.Originality/Value: The present study examines the impact of environmental innovations in the home appliance industry, which is one of the high-consumption and environmentally impactful industries. Additionally, the study specifically investigates the mediating role of ethical aspects, which has been less addressed in the research literature.